Acute Vision Loss After Ophthalmic Artery Embolization of Meningioma. Issue 4 (December 2019) - Torres, Guadalupe; T. Kini, Ashwini; Al Othman, Bayan; Lee, Andrew G.
Abstract : Abstract: A 40-year-old man presented with acute-onset painless visual loss after preoperative embolization for a large skull base meningioma through the ophthalmic artery. We describe the clinical presentation of an isolated ipsilateral afferent and efferent pupillary defect in this patient who had radiographic documentation of embolization material in the intraorbital ophthalmic artery. Although ophthalmic and retinal artery occlusions have been described previously after endovascular embolization, our patient had a unique clinicoradiologic presentation.